2020
DOI: 10.1177/0081246320978969
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the unemployed from selected communities in South Africa based on their experiences, commitment to employment, and job search behaviour

Abstract: Unemployment has negative consequences for individuals’ psychological well-being. Consequently, interventions should be designed and implemented to alleviate the psychological burden of unemployment. The design of these interventions should, however, be approached with care, as ‘the unemployed’ may not be a homogeneous group. The aim of the study was to determine whether the four already identified (the optimists, the desperate, the discouraged, and the adapted) South African unemployment profiles could be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The motivated, furthermore, reported (the most) positive affective experiences, whereas, the ambivalent reported the least positive experiences. Experiencing unemployment as both negative and positive may be unusual, but is not entirely uncommon [see (24,25)]. Again, our findings showed the detrimental effect of perceiving the environment as constraining while being motivated to find a job.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The motivated, furthermore, reported (the most) positive affective experiences, whereas, the ambivalent reported the least positive experiences. Experiencing unemployment as both negative and positive may be unusual, but is not entirely uncommon [see (24,25)]. Again, our findings showed the detrimental effect of perceiving the environment as constraining while being motivated to find a job.…”
Section: Discussionmentioning
confidence: 58%
“…As the opposite of the ambivalent group, this finding confirmed that even in the absence of barriers (resulting in amotivation), some unemployed individuals might still not be motivated to search for a job. It might be that these individuals had adapted to unemployment (24,25) and/or had withdrawn from the labor market (67,68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Internet+" integrates the Internet with traditional industries in-depth and creates a new development ecology by utilizing various information and communication technologies as well as through a variety of Internet platforms, which has six characteristics, such as cross-border integration, innovation-driven, reshaping structure, respecting life, open ecology, and connecting everything [1][2][3]. The era of "Internet+" not only profoundly affects the development of national society and economy but also brings great challenges and opportunities to the employment of college students [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nanhui Gong and Bosen Yang. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] …”
mentioning
confidence: 99%